Immunization with a live, attenuated simian immunodeficiency virus (SIV) prevents early disease but not infection in rhesus macaques challenged with pathogenic SIV. - Marthas, M L (1990)
An infectious, virulence-attenuated molecular clone of simian immunodeficiency virus (SIV), SIVMAC-1A11, was derived from an SIV isolate that causes fatal immunodeficiency in rhesus macaques. When inoculated intravenously in rhesus macaques, SIVMAC-1A11 induced transient viremia (1 to 6 weeks) without clinical disease and a persistent humoral antibody response. The antibodies were directed mainly against the viral envelope glycoproteins, as determined by immunoblots and virus neutralization. The potential of this virulence-attenuated virus to protect against intravenous challenge with a pathogenic SIVMAC strain was assessed. Five rhesus macaques were each given two intravenous inoculations with SIVMAC-1A11 7 months apart. Three of the five immunized monkeys and four naive control animals were then challenged with 100 to 1,000 100% animal infectious doses of pathogenic SIVMAC. All seven animals became persistently viremic following the challenge. Four of four unimmunized animals developed severe clinical signs of simian acquired immunodeficiency syndrome by 38 to 227 days after challenge and were euthanatized 91 to 260 days postchallenge. However, no signs of illness were seen in immunized monkeys until 267 to 304 days postchallenge, when two of three immunized animals developed mild thrombocytopenia and lymphopenia; one of these animals died with clinical signs of simian immunodeficiency disease at 445 days after challenge. The two SIVMAC-1A11-immunized monkeys that were not challenged were healthy and antibody positive 22 months after the initial immunization. Thus, although live SIVMAC-1A11 was immunogenic and did not induce any disease, it failed to protect rhesus macaques against infection with a moderately high dose of pathogenic virus. However, immunization prevented severe, early disease and prolonged the lives of monkeys subsequently infected with pathogenic SIV.